The Evaluation Of Independent Norm Text And Impartial Judge On The Constitutional Court Of Indonesia - N Nadir; Win Yuli Wardani (Fakultas Hukum, Universitas Warmadewa, 2019)
In this paper, the Judge of the Constitutional Court is the authority of judicial power to enforce law and justice as a guardian and interpreter of the constitution. The method used in this research is legal research. The result of this research is that the evaluation of the independent and impartial texts of Indonesian constitutional court judges can be measured from procedural independent, legal fomal-empirical independent, and empirically independent either according to national legal instruments or international instruments. Meanwhile, the supervision of the Constitutional Court judges is devided into two supervisory models. These are that it is supervised by the Ethics Council of the Constitutional Court and by the Honorary Council of Constitutional Justices. For the external supervision, the court is supervised by the Constitutional Court with the Judicial Commission philosophically forming the Ethics Council to perform the (control function) to the judges of the Constitutional Court in order to avoid deviation of legal norms by the judges of the Constitutional Court Indonesia.